Post-Coronavirus Disease 2019 (COVID-19) Liver Injury in Pregnant Women: A Retrospective Cohort Study - Yannan Gu; Ying Xing; Jing Zhu; Li Zeng; Xiaohong Hu (Clinical and Experimental Obstetrics & Gynecology)
Background: Coronavirus Disease 2019 (COVID-19) has risen as a global threat to public health and can cause both respiratory and multisystemic diseases in humans. This study aimed to describe the incidence of abnormal liver function tests (LFTs) in post-COVID-19 pregnant women, and to explore characteristics of pregnant women with abnormal LFTs. Methods: This retrospective cohort study comprised 155 pregnant patients who experienced COVID-19, alongside 76 uninfected pregnant women as a control group. All participants were randomly selected from the Obstetrics outpatient clinic at the Affiliated Maternity and Child Health Care Hospital of Nantong University between December 25 2022 and January 31 2023. Demographic data and laboratory data were collected, and results were statistically analyzed. Results: Of the 155 pregnant women who had experienced COVID-19, 63 (40.6%) showed abnormally raised liver enzymes. In the control group, 9 (11.8%) cases had abnormal LFTs. Differences between the two groups were statistically significant (p < 0.05). Of the 63 post-COVID-19 patients with abnormal LFTs, the median serum level of alanine transaminase (ALT), aspartate transaminase (AST), and alkaline phosphatase (ALP) was: 175 U/L (range, 51–352 U/L), 113 U/L (range, 42–329 U/L), and 123 U/L (range, 35–250 U/L). Median total biliary acid (TBA) was 18.1 µmol/L (range, 1.8–33.5 µmol/L). The patients who developed abnormal LFTs did so within 7–14 days after contracting COVID-19, with a median of 10 days. Subsequently, their liver function returned to normal within 4–26 days, with a median of 12 days. The univariate analysis on factors that may affect abnormal LFTs revealed a statistically significant difference in gestational age and body mass index (BMI) (p < 0.001). Logistic regression analysis found that gestational age (odds ratio (OR): 1.095 [1.021–1.174]) and BMI (OR: 1.169 [1.059–1.289]) remained a significant independent risk factors for liver injury (p < 0.05). Conclusions: Pregnant women are at an increased risk of liver injury after contracting COVID-19. Moreover, with the increase of gestational age and BMI, the risk of liver injury increases.